Igorin haitari. - Siiskonen, Minna; Pöljö, Esa; Hämäläinen, Jukka; Hämäläinen, Tuomo (Tuomo Heikki Kalevi) (2000)
1 kappale.
Siiskonen, Minna (lauluääni).
PUUTELUETT.
Puuttuu kansalliskokoelmasta
[Äänite].
Keywords: iskelmät